Final Report of the Pensions Working Group, July 2005 (Central Bank of Malta, 2005)
The Pensions Working Group, following the launch of the White Paper on Pensions reform tabled by the Prime Minister in the House of Representatives on 24th November 2004, carried out an extensive and embracing national consultation and discussion process where-in it held 39 sessions with various stakeholders and 17 sessions with the media. The Group received 47 formal submissions following the closure of the consultation and discussion process at the end of April 2005. During the period of the consultation and discussion process the Group continued with its work and four major studies were carried out. These are the Economic Impact Assessment, the Social Impact Assessment, the Actuaries Assessment, and the Survey on people's perceptions on the pensions system and pensions reform. This work was placed in the public domain following a Press Conference which the Group held on 23rd April 2005. It is pertinent to underline that the feedback received was unanimous in the fundamental conclusion that an option of 'no reform' to the current pensions system is not a solution. This conclusion confirms the Group's position as stated in the White Paper that a reform of the pensions system is a paramount necessity if pensions for future generations are to be both adequate and sustainable. It also should be stated that the feedback received agreed that the White Paper was a good basis upon which mature discussion could be carried out on the reforms necessary to attain an adequate and sustainable pensions system. As expected, the feedback received was at times in agreement, in part or in whole, and at times in disagreement, in part or in whole, with the recommendations presented in the White Paper. (...)
Keywords: 330